POLITICAL THEORY OF SECESSION: SOME ASPECTS OF THE KOSOVO CASE - Krnetic, Helena Lj (Politeia, 2023)
Summary      In this paper, we will try to test the dominant political theory of secession, namely the countractualist one, in one specific case - the secession of Kosovo. This case is particularly important because it represents the most important, if not the only, exception of the dominant political theory of secession and the existing political practice of secessionist movements as well. Obviously, this exceptionality must be based on some other basis. One possible claim is the "historical" basis of independence. In this text, we will test this argument and show its unsustainability.
Keywords: Key words: political theory, sovereignty, consent, secession, Kosovo